Humanistic Active Learning as a Student-Centered Approach to Improving Academic Achievement in Islamic Religious Education - Hasnita Hasnita; Amir Patintingan; Muhammad Naim; St. Warda Hanafie Das; Suredah Hamid (Journal of Education and Learning Sciences, 2026)
The integration of humanistic learning theory and active learning has become increasingly important in promoting student-centered instruction within Islamic Religious Education (IRE). However, empirical evidence regarding how these complementary approaches improve students' academic achievement and classroom engagement in authentic school settings remains limited. This study investigates the implementation of humanistic theory integrated with active learning and examines its contribution to improving students' learning experiences and academic achievement in Islamic Religious Education. A qualitative case study was conducted at a public junior secondary school in South Sulawesi, Indonesia. Participants included the school principal, Islamic Religious Education teachers, homeroom teachers, and students who were purposively selected based on their involvement in the instructional process. Data were collected through classroom observations, semi-structured interviews, and document analysis and were analyzed using the interactive model of Miles, Huberman, and Saldaña involving data condensation, data display, and conclusion drawing. The credibility of the findings was ensured through source triangulation, method triangulation, prolonged engagement, and member checking. The findings indicate that integrating humanistic principles with active learning creates a more democratic, interactive, and supportive learning environment that promotes student participation, self-confidence, conceptual understanding, collaboration, and academic achievement. Teacher pedagogical competence, positive classroom interaction, and learner-centered instructional practices emerged as important supporting factors, while limited instructional time, differences in students' readiness, and inadequate learning facilities remained major challenges. This study contributes to contemporary Islamic education by demonstrating that integrating humanistic learning with active learning provides an effective pedagogical framework for enhancing both academic achievement and holistic student development. The findings also offer practical guidance for teachers and educational policymakers seeking to strengthen student-centered learning in Islamic Religious Education.